2015
DOI: 10.1371/journal.pone.0134502
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Shifts in Leaf-Litter Ant Assemblages (Hymenoptera: Formicidae) across Ecosystem Boundaries Using Multiple Sampling Methods

Abstract: Global or regional environmental changes in climate or land use have been increasingly implied in shifts in boundaries (ecotones) between adjacent ecosystems such as beech or oak-dominated forests and forest-steppe ecotones that frequently co-occur near the southern range limits of deciduous forest biome in Europe. Yet, our ability to detect changes in biological communities across these ecosystems, or to understand their environmental drivers, can be hampered when different sampling methods are required to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…The results of this study underline that the outcome of taxonomic inventory or estimation of functional composition and diversity depends on selected sampling methods (Wiezik et al 2015;Lee and Guénard 2019). In our opinion, relying on a single method can strongly bias obtained results (see Wiezik et al 2015;Hanisch et al 2018). Thus, we recommend using an integrated approach that includes several complementary methods suitable for the studied habitat, especially when a survey aims to assess a-, b-, and cdiversity.…”
Section: Advantages and Disadvantages Of Ptm And Hcmmentioning
confidence: 88%
See 2 more Smart Citations
“…The results of this study underline that the outcome of taxonomic inventory or estimation of functional composition and diversity depends on selected sampling methods (Wiezik et al 2015;Lee and Guénard 2019). In our opinion, relying on a single method can strongly bias obtained results (see Wiezik et al 2015;Hanisch et al 2018). Thus, we recommend using an integrated approach that includes several complementary methods suitable for the studied habitat, especially when a survey aims to assess a-, b-, and cdiversity.…”
Section: Advantages and Disadvantages Of Ptm And Hcmmentioning
confidence: 88%
“…Pitfall traps can be used only in localities with well-developed soil or litter layer, and they detect only a particular group of ants (Romero and Jaffe 1989;Sheikh et al 2018). This method seems to be insufficient in rocky, steep, or flooded areas and is not applicable in anthropogenic habitats (Gotelli et al 2011;Wiezik et al 2015). PTM requires also revisiting the same sampling area.…”
Section: Advantages and Disadvantages Of Ptm And Hcmmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the number of ant species associated primarily with forest habitats (e.g., F. truncorum, M. ruginodis, and L. platythorax) was the highest in grassland dolines, whereas only one species (M. ruginodis) with few occurrences was observed in forested sites. In Central Europe, Fagus sylvatica forests with lowresource availability are among the most species poor habitats, usually with only a few ant species and very low population densities (Dolek et al, 2009;Wiezik et al, 2015). In our previous study (Bátori et al, 2019), we detected a significant effect of slope exposure on ant species composition within the grassland dolines in the Bükk Mts (e.g., M. ruginodis dominated the north-facing slopes).…”
Section: Modelmentioning
confidence: 68%
“…For instance, the presence of grassland patches in forested landscapes may support the maintenance of high ant diversity and facilitates the persistence of several species that cannot survive in shady habitats (Dolek et al, 2009). In contrast, homogenous habitats (e.g., Fagus sylvatica forests with low resource availability) create unfavourable conditions for many ants (Dolek et al, 2009;Wiezik et al, 2015). Results of the abovementioned studies suggest that habitat heterogeneity and related vegetation patterns may influence the composition of ant assemblages in current and potential microrefugia by filtering their functional traits, resulting in a relationship between the functional diversity of assemblages and small-scale environmental conditions (cf.…”
Section: Introductionmentioning
confidence: 99%